2012 Asia-Pacific Power and Energy Engineering Conference 2012
DOI: 10.1109/appeec.2012.6307309
|View full text |Cite
|
Sign up to set email alerts
|

Size Optimizations to the Stress Cones in 48kV XLPE Cable Terminations

Abstract: It was described the size optimizations to the stress cones as which were key structre parts in the 27.5/48 kV XLPE cable heat/cold shrinkable combinated terminations, aslo included the effection performance to the elctric field strength by adjusted the radius to the innnerside bend surface of the stress cones. The result were indicated that the optimization could be applied for the designing and checking for the stress cones. I INTRODUCTIONAs a key components of the power cable heat and cold shrinkable combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Improving the design of cable terminal plays an important role in improving the overall properties of cable [2]. The electric field distribution in the terminal can be controlled by optimizing the size of the stress cone [3] and using the stress control tube [4]. It is found that the selection of reinforced insulating materials in cable terminal will directly affect the distribution of field strength in terminals [5].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the design of cable terminal plays an important role in improving the overall properties of cable [2]. The electric field distribution in the terminal can be controlled by optimizing the size of the stress cone [3] and using the stress control tube [4]. It is found that the selection of reinforced insulating materials in cable terminal will directly affect the distribution of field strength in terminals [5].…”
Section: Introductionmentioning
confidence: 99%